Legal protection for whistleblowers in uncovering fraud in government - Raodahtul Odha Jannah; Suhartono Suhartono; Farid Fajrin; Roby Aditiya (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to examine the extent to which whistleblowers play a role in detecting fraud in government and how the legal system in Indonesia provides protection for whistleblowers. This study uses a type of qualitative research with a library research approach.namely binding legal materials consisting of basic regulations (the 1945 Constitution of the Republic of Indonesia and its amendments regarding the protection of a whistleblower in exposing). , fraudin government, as corruption is rampant so that it is appropriate for whistleblowers to receive legal protection Provisions for legal protection for whistleblowers are implicitly contained in Law Number 13 of 2006 concerning Witness and Victim Protection Institutions and SEMA Number 2011 concerning Treatment of Actors (Persons), Complainant) and Author Witnesses who work together (Justice contributors). The types of whistleblowers provided by Indonesia are physical and psychological protection, special treatment when testifying in court, protection of legal status, and the possibility of compensation in the form of leniency.